Current Trends of Acute Poisoning Reporting at Private Medical Center of Rural Sindh (Medical Forum Monthly, 2024)
Objective: The present study intends to evaluate the current trends of acute poisoning reporting at private medical center of Rural SindhStudy Design: Descriptive/Retrospective studyPlace and Duration of Study: This study was carried out at Murk General Hospital Tando Adam from January through December 2012.Materials and Methods: Sixty patients with a history of poisoning were studied. The diagnosis of poisoning was based on history of patients as disclosed by relatives, clinical findings, investigations and response to treatment. The age, sex, social class, cause and types of poison were noted. The data was collected on a proforma. The variables were typed on SPSS version 21 for analysis.Results: The mean age of subjects was 33±7.5 years. The most affected age group was 20-29.9 years (n=43) (71.6%). Of sixty subjects, 23(38.3%) were male and 27 (61.6%) female. (p=0.001). Of sixty subjects, 75% (n=45) are farmers belonging to lower social class of rural population, suffering from organophosphate pesticide poisoning (48.3%). Comparing rural to urban population, it shows rural population is suffering more; 88.3% (n=53) vs. 11.6% (n=7). The frequency of organophosphate poisoning is found high 48.3% (n=29) in patients coming from rural areas usually farmers. The accidental organophosphate poisoning is found most frequent in rural population. The alcohol is the second most frequent cause of acute poisoning found in 18.3% of cases.Conclusion: Incidence of accidental poisoning is found very high from organophosphate pesticides. Sale of drugs, Diazepam and Alprazolam, must be prohibited without proper prescription. It is recommended that measures may be taken to make aware the farmers for using the organophosphate pesticides properly.